A review of global postharvest loss assessments in plant-based food crops: Recent findings and measurement gaps - Kitinoja, Lisa; Tokala, Vijay Yadav; Brondy, Amanda (Journal of Postharvest Technology, 2018)
Since the FAO “Global Food Losses and Food Waste” report in 2011 estimated one-third of all the food produced globally was being lost, researchers have been using many different methodologies to assess and measure postharvest food loss and waste. Several international research organizations and large-scale projects have included postharvest loss assessments in their project agendas, and hundreds of journal articles have been published. Estimated losses have been determined and reported in several different ways, including quantitative losses, qualitative losses, and economic losses. This review provides an overview of the measurement methods and findings of 268 postharvest loss assessment studies on plant-based crops from around the world.